Synthesis of Bioplastics on Rice Straw Cellulose Using Orange Peel Extract, Chitosan, and Sorbitol - Sitti Chadijah; Harianti Harianti; Amalyah Febryanti; Alfiah Alif; Maulidiyah Maulidiyah; Akrajas Ali Umar (Walisongo Journal of Chemistry, 2022)
With the use of several plasticizers (orange peel extract, chitosan, and sorbitol), rice straw cellulose has been used to synthesize and characterize bioplastics. This study aims to synthesize and characterize bioplastics from rice straw cellulose with various additions of plasticizers, namely orange-peel extract, chitosan, and sorbitol, each with a certain concentration so that quality improvement can occur. The methods used in this study include testing the tensile strength value, testing the percentage elongation, and testing the percentage of biodegradation. In addition, functional group characterization tests were also carried out using FTIR. The results obtained in this study were the best values for tensile strength and percentage elongation in treatment A, namely 10.2611 MPa and 13.88%. The percentage of biodegradation for 7 days reached 50.58%. Functional group absorptions were found in various plasticizers, namely C-H, O-H, C-O, C-N, and C=C. Based on existing data, bioplastics synthesized using rice straw cellulose in various plasticizers meet JIS (Japan Industrial Standards).